Material and Technological Aspects while Processing of Selected Ultra High Strength Steel - Barényi, Igor; Majerík, Jozef; Bezecný, Ján; Krbaťa, Michal; Sedlák, Josef; Jaroš, Aleš (Manufacturing Technology Journal, 2019)
This authors presented article deals with the size of heat affected zone (HAZ) at specific technological processes (cutting and welding techniques). Armox 500 steel was selected and used to perform all realized experiments. Even before the start of the experiments that investigated the effect of HAZ on cutting and welding, it was necessary to subject the investigated Armox 500 steel to basic experimental measurements with regard to its chemical composition, fundamental microstructure and mechanical properties. The microstructure was performed on Neophot 32 optical microscope. Chemical composition was analysed on the spectral analyzer Spectrolab Jr CCD. Mechanical properties, like nanohardness H and reduced Young modulus Er were subsequently measured on Hysitron TI950 Triboindenter with a Cube Corner measuring tip, and evaluated by software Triboscan. Based on the measured values, a 2D nanostructure of the distribution map of s H and Er was evaluated in Matlab. This scientific research, together with all measured and calculated results, is the fundamental that will help to optimizing the quality and used all these results to optimize presented material and technological processes.
Keywords: Armox 500 steel; mechanical properties; microstructure; cutting; welding